The Importance of Appraisal and Professional Association for Creative Economy Business Actors - Uswatun Hasanah; Hardianty Munawir (IJIBE (International Journal of Islamic Business Ethics), 2018)
In the era of globalization and technological advances, the development of creative economy is moving rapidly and offering much more different career for economic actors. But, this development of creative economy has some problems. The examples are the fluctuation of cash flow on the creative economy business actors and wealth authority which belong to intangible assets. Thus, it is difficult to determine the average price of a work from creative economic actors. According to the library researches, this study found the things that can solve the problem of a work standarization price for creative economy business actors. The creative economy business actors can be called as freelancer. They can make appraisal program under protection of professional association as policy maker and law protector to protect the value of a work from creative economy business actors.keywords:  Creative    Economy    Business    Actors,    Appraisal, Professional Association